Abdominal and pelvic vascular trauma in Queensland, Australia: institutional experience at a level one trauma centre - Bowles, Madison; Weller, Justin (International Surgery Journal, 2021)
Background: Abdominal and pelvic vascular injuries are amongst the most lethal injuries sustained by trauma patients. Unlike internationally, the epidemiology is not well documented in Australia. Gold Coast University Hospital (GCUH) is a level one trauma centre in Queensland, Australia. This study aims to identify the epidemiological patterns of abdominal and pelvic vascular traumatic injuries, their interventions and outcomes, and compare these with national and international data. Methods: All individuals who presented to GCUH between January 2014 and December 2019 with abdominal or pelvic vascular injuries were retrieved from the GCUH prospective trauma database. A descriptive analysis was undertaken on this cohort. Results: The study reviewed 5452 trauma admissions to GCUH, of which 68 patients sustained abdominal or pelvic vascular injuries. The number of blunt and penetrating trauma cases were 53 (77.9%) and 15 (22.1%) respectively, and 51 (75%) of the patients were male. Interventions were required in 57 patients (83.8%). Of these interventions, 28 were open (41.2%), 27 were endovascular (39.7%) and 2 required both open and endovascular interventions (2.9%). The most commonly injured vessels were the visceral arteries (51.9%) and iliac arteries (22.7%). The mortality rate was 8.8% which were all as a result of blunt trauma. Conclusions: Abdominal and pelvic vascular trauma causes significant injuries with a higher mortality than general trauma. Given the majority of cases occurred secondary to road accidents, motor vehicle safety interventions and prevention programmes are likely to have the greatest effect on reducing the abdominal and pelvic vascular injury rate in Australia.